2017
DOI: 10.1111/plb.12658
|View full text |Cite
|
Sign up to set email alerts
|

Changes in floral biology and inbreeding depression in native and invaded regions of Datura stramonium

Abstract: ABSTRACT• Plant populations invading new environments might compromise their fitness contribution to the next generation, because of the lack of native specialist pollinators and/ or potential mates. Thus, changes in plant mating system and traits linked to it are expected in populations colonising new environments where selection would favour selfing and floral traits that maximise reproductive output. To test this, we studied native (Mexico) and non-native (Spain) populations of the obligate sexual reproduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…From these studies, we know that inbreeding depression is typically severe for species that have mixed mating systems (i.e., plants that both self and cross fertilize) and that mixed mating is common in flowering plants (Goodwillie et al., ). Scores of additional studies have shown that inbreeding depression is one of the primary forces that shape the evolution of floral traits such as herkogamy, dichogamy, molecular systems of self‐incompatibility, enantiostyly, inflorescence architecture, and floral display (Jiminez‐Lobato et al., ) and is the primary force in the evolution of sexual systems such as monoecy and dioecy (Johnson et al., ). Moreover, inbreeding depression is a key force in virtually all models for the evolutionary trajectory of plant mating systems.…”
mentioning
confidence: 99%
“…From these studies, we know that inbreeding depression is typically severe for species that have mixed mating systems (i.e., plants that both self and cross fertilize) and that mixed mating is common in flowering plants (Goodwillie et al., ). Scores of additional studies have shown that inbreeding depression is one of the primary forces that shape the evolution of floral traits such as herkogamy, dichogamy, molecular systems of self‐incompatibility, enantiostyly, inflorescence architecture, and floral display (Jiminez‐Lobato et al., ) and is the primary force in the evolution of sexual systems such as monoecy and dioecy (Johnson et al., ). Moreover, inbreeding depression is a key force in virtually all models for the evolutionary trajectory of plant mating systems.…”
mentioning
confidence: 99%
“…In novel or unfavourable environments, flowering plants show reduced reproductive fitness and low reproductive output 14 , 15 . In Datura stramonium , flowers exhibited reductions in herkogamy and pollinator visits in the nonnative range compared to the native environment 13 . Moreover, Ferula jaeschkeana exhibited variable responses in different native and invasive environments with favourable performance.…”
Section: Introductionmentioning
confidence: 95%
“…Plant species experience these abiotic conditions either in duration, magnitude or in combination in a new range, which leads to a decrease in population size/density, genetic diversity, and the outcrossing rate, an increase in homozygosity within the population, and adaptive evolution of traits under new ecological conditions 11 , 12 . However, regardless of the negative impact expected by the reduction in genetic diversity, some introduced species perform successfully in the new distribution ranges 13 . In novel or unfavourable environments, flowering plants show reduced reproductive fitness and low reproductive output 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Jiménez‐Lobato et al . () report a comparative study between Mexican and southern Spanish populations and found that phenotypic selection on stigma–anther separation is released in invaded populations, in comparison with native populations. The latter show some inbreeding depression, which is consistent with the hypothesis of evolution of invasiveness.…”
Section: A Centre Of Concern For Conservation Sciencementioning
confidence: 99%